Identifying and evaluating human errors in Operating a Furnace in a Petrochemical Industry Using Human Event Analysis Technique (ATHEANA) - fereshteh Jahani; Bahram Kouhnavard; Zohreh Jafarzadeh (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction:   Industrial accidents are among the major problems of today's societies. Studies on accidents indicated that the most important cause of their occurrence was the human factor. Therefore, the purpose of this study was to identify and evaluate human error in the operation of furnace using the human event analysis technique in a petrochemical industry. Methods: This was a qualitative and cross-sectional study which was analyzed by directly observing the activities, interviewing the analysis, and reviewing the documents and instructions, tasks and sub-tasks by Hierarchical task analysis (HTA) method, and the results were provided in HTA charts. In the next step, according to Technique for Human Error Analysis (ATHEANA) instructions, the relevant worksheet was completed. Results: The results indicated that coil breakage or precision instrument connections, improper bypassing of pressure in the paths to rotate the furnace to the atmosphere, or process and leakage of gas lines, flanges and valves whose probability of defect was 0.20, 0.14 and 0.13, respectively, had the highest probability of error. The probability of human error in the operation of the furnace was calculated to be 0.63. Conclusion: Applying corrective measures such as: selecting skilled people, holding training courses, routine monitoring of temperature, pressure measuring equipment, etc. for proper operation of the apparatus and visual monitoring of all furnace parts, including valves, are some of the things with which the likelihood of human error in the operation of the furnaces was reduced.